Analyzing the Underlying Factors of Indonesia's Decision to Sign the Indonesia-Peru Comprehensive Economic Partnership Agreement (IP-CEPA): Menganalisis Faktor-Faktor Dasar di Balik Keputusan Indonesia untuk Menandatangani Perjanjian Kemitraan Ekonomi Komprehensif Indonesia-Peru (IP-CEPA) - Diphda, Bintang Corvi; Elnathan, Andrew; Arianto, Delvin Pramatya; Muhammad, Najmil; Hafizh, Sultan Baariq (DAS Institute, 2025)
This article explains why Indonesia decided to sign the Indonesia-Peru Comprehensive Economic Partnership Agreement by applying Solis and Katada’s three-motive lens: economic, security, and leverage. The study uses a qualitative desk review with thematic analysis and triangulation of official documents, negotiation records, and 2020-2025 trade statistics. The case shows a rapid process from the first formal round in May 2024 to the conclusion in August 2025 and signature on 11 August 2025. Economically, the agreement addresses discrimination risks by removing most tariffs at entry into force, with Peru covering about 90,68% of lines and Indonesia about 92,26%, and by clarifying rules of origin, customs, and cooperation on technical barriers to trade and sanitary and phytosanitary measures. Security motives are visible in the presidential ceremony tied to 50 years of diplomatic relations, a joint declaration, and a parallel cooperation memorandum that widens cross-regional engagement with an American Latin partner. Leverage motives appear in goods-first sequencing, reusable chapter designs, and committee structures that build capacity for later talks. This further implies the need for further policy adjustment from the Indonesia government in terms of adjusting the implementation process, providing a comprehensive help desk, and improving coordination among various stakeholders.